The Impact of Work Skills Development on Prisoners Readiness to Reintegration into Society (Case Study in Narcotics Correctional Institution Class II A Pangkalpinang) - Syahfa Rizi Rasta Buana; famelinda, Famelinda Carera; Briely Daffa Aufan; Dwi Haryadi (Unram Law Review, 2025)
The correctional system aims to transform prisoners into complete individuals, admit mistakes in the past, try to improve themselves, and not repeat criminal acts. Based on Law Number 22 of 2022 concerning Correctional, also known as (Undang-Undang Nomor 22 Tahun 2022 tentang Pemasyarakatan), the guidance provided to prisoners includes various forms of personality development, which include fostering religious, national and state awareness, increasing intellectual abilities and legal understanding, and fostering independence. This research uses a qualitative descriptive approach, which is used to describe actual conditions in the field regarding the development of independence through job skills training. The authors use secondary data to compose the article. The research results at the Narcotics Correctional Institution Class II A Pangkalpinang show that the coaching activities in the prison, which focus on developing personality and independence, follow Law Number 22 of 2022 concerning Correctional. Most ex-convicts have applied the work skills previously provided by the Narcotics Correctional Institution Class II A. Therefore, it has successfully distributed work skills training to prisoners so that when they leave, they can immediately apply the training that has been provided.